„Biuletyn Historii Wychowania” (1995–2024) z okazji publikacji jubileuszowego – 50 tomu - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2026)
The article aims to analyze the content and history of one of the most important Polish academic journals in history of education, history of schools, and pedagogical thought. The Bulletin of the History of Education has been on the publishing market since 1995. It is an organ of the Main Board of the Society for the History of Education. At the same time, it is published by the renowned publishing house of the Poznan Society of Friends of Learning in cooperation with the Faculty of Educational Studies of Adam Mickiewicz University. It is also the only Polish academic journal publishing an up-to-date bibliography of its scientific discipline each year. The topics of the published articles are very broad, both in a chronological sense – from antiquity to modern times – and geographically: from civilizations of ancient Egypt and the Middle East, to Europe and Poland, as well as in the field of issues and approaches (including the methodology, source, historiographic or statistical ones). The list of topics is dominated by the history of upbringing and education and the history of various educational institutions. Several papers published in Bulletin can be described as interdisciplinary studies on the border of humanities and social sciences.